Termination of Prosecution Based on Restorative Justice in Indonesia it is Associated with the Renewal Criminal Law - Fajar Rudi Manurung; Topo Santoso; M. Eka Putra; Marlina Marlina (Green Publisher, 2024)
Criminal acts arise from various aspects of human activity, including the political, social and economic spheres. The success of law enforcement is traditionally measured by the ability to bring criminals to justice and impose appropriate penalties. However, in certain minor cases, such as theft, embezzlement, and fraud with minimal losses, the public questions the need for prosecution, as they believe that prosecution does not match the seriousness of the offense. The purpose of this study is to analyze the implications and effectiveness of prosecution discontinuation based on restorative justice in the Indonesian legal framework. Using a qualitative research approach, this study examines the regulatory structure and practical application of restorative justice in Indonesia. Data was collected through document analysis and interviews with legal practitioners to explore alignment of regulations with legal principles and community expectations. The research findings show that, although restorative justice offers a viable avenue to achieve peace between offenders and victims, its implementation in Indonesia is still limited, as it is not yet embedded in the broader criminal law system. Currently, peace agreements between the parties are only considered as a mitigating factor in the sentencing process. This research suggests that stronger legal legitimacy for restorative justice, such as the inclusion of restorative justice into the Draft Criminal Procedure Code is essential to adapt to the evolving legal culture and public expectations. The implications of this research highlight the need for comprehensive criminal law reform to ensure justice that aligns with societal values and contemporary legal standards.